Pengembangan Instrumen Kemampuan Berpikir Kreatif Dalam Menghitung Volume Bangun Ruang Kelas V MIN 4 Kota Medan - Nabilah Azrilia; Fathiyah Rahma; Siti Khadijah; Ade Syam Fitri; Winda Winda; Dinda Dinda; Habib Syarkowi; Mia Hafizah Tumangger (Politeknik Kampar, 2024)
This research aims to develop an instrument for assessing the creative thinking abilities of fifth grade students at MIN 4 Medan City in calculating the volume of spatial shapes. Using development methods and quantitative approaches, 60 students consisting of 27 men and 33 women became subjects on November 17 2023. The results show the instrument has 100% validity and a high level of reliability (Cronbach's Alpha = 0.893). Item and scale analysis provides in-depth insight into the characteristics of the instrument, with several items standing out as strong indicators. It is hoped that this instrument can effectively support mathematics teaching at MIN 4 Medan City by providing an accurate picture of students' creative thinking abilities in calculating the volume of geometric figures.